Protocol for a mixed-methods randomised controlled trial evaluating the psychosocial effects of an expressive arts-based intervention on adults with age-related macular degeneration - Qing Li; Temmy Lee Ting Lo; Rainbow Tin Hung Ho; Adrian Ho Yin Wan; Ted Chun Tat Fong; Caitlin Kar Pui Chan; Allen Ming Yan Cheong; Wai Chi Chan (BMJ Open)
Introduction Age-related macular degeneration (AMD) is a prevalent eye disease among middle-aged and older adults. AMD leaves the patient with irreversible deteriorating vision, which profoundly impacts their daily lives and psychosocial well-being. Given the limited studies addressing the psychosocial needs of adults with AMD and, in particular, using an expressive arts-based intervention (EXABI) as an intervention, this study aims to investigate the effectiveness of such an intervention in enhancing the psychosocial well-being of adults with AMD.Methods and analysis This study will employ a mixed-methods randomised controlled trial design. One hundred fifty-four participants with AMD will be recruited and randomised into either the EXABI or treatment-as-usual waitlist control group. Participants will respond to a battery of measurements regarding their psychosocial condition at four time points: baseline (T0), 2 months after baseline (postintervention, T1), 5 months after baseline (T2) and 8 months after baseline (T3). A subgroup of participants will also share their experiences through in-depth interviews at T1 and T3 to help further understand the mechanism and effect of the intervention. Quantitative data will be analysed by mixed-effects models and path analysis, whereas qualitative data will be analysed by adopting the thematic analysis approach. The two sets of data will be integrated to provide a comprehensive view of the effectiveness and mechanisms of the intervention.Ethics and dissemination This study has obtained ethical approval from the Human Research Ethics Committee of the University of Hong Kong (Ref. no.: EA210606). All research procedures will be conducted upon receiving signed written consent forms from participants. The findings of the study will also be presented at international conferences and published in peer-reviewed academic journals.Trial registration number NCT05675150, prospectively registered.